Strategi Pembelajaran Bahasa pada Anak Usia Dini di Lembaga PAUD: Studi Literatur - Aura Angelina; Annisa Cahya Wulandari; Shifa Aulia Salsabila; Salsabila Ananda Putri; Aisyah Syakirah; Pira Pratiwi; Amanda Maharani (Early Stage, 2026)
Language development is an important aspect of early childhood education because it supports children’s communication, thinking, social interaction, and learning readiness. This study aims to analyze language learning strategies for early childhood in PAUD institutions through a literature review. The study used a narrative thematic synthesis approach by examining journal articles, proceedings, and academic books related to early childhood language development, learning strategies, learning media, bilingual and multicultural learning, social environment, teacher roles, and implementation challenges. The findings show that language learning strategies in PAUD are implemented through storytelling, interactive storytelling, picture stories, language games, movement and songs, concrete media, puzzles, busy books, second language learning, multicultural learning, and social interaction-based activities. These strategies support listening skills, vocabulary mastery, speaking confidence, expressive language, and social communication when applied through concrete, interactive, enjoyable, and developmentally appropriate activities. However, language learning in PAUD still faces challenges, including limited media, limited time, differences in children’s language abilities, gadget use, and lack of parental support. Therefore, language learning should be designed collaboratively by teachers, families, and institutions to create a language-rich learning environment.